External Hemipelvectomy Pelvic Ring Stabilization: The Unique Application of Chimeric Lower Extremity Pedicled Fillet Flaps - Talarczyk, Matthew R.; Boehmler, James H.; Ljungquist, Karin; Tiwari, Pankaj; Mayerson, Joel L.; Miller, Michael (Journal of Reconstructive Microsurgery, 2013)
Reconstruction of large external hemipelvectomy oncologic defects of the proximal limb and trunk remains a formidable surgical challenge. Large pelvic defects can result in exposed bones, neurovascular structures, and surgical hardware due to a paucity of soft tissue coverage. When the size of a hemipelvectomy defect precludes coverage by local posterior- or anterior-based hemipelvectomy flaps, the use of other local flaps must be considered before resorting to free tissue transfer. The rectus abdominis myocutaneous pedicled flap is the most commonly used locoregional flap for soft tissue coverage of large hemipelvectomy soft tissue defects. The concept of utilizing parts from otherwise nonsalvageable limb components in reconstruction is well described in the literature and referred to as the “spare parts” concept. Utilization of these distal “spare parts” has the advantage of obtaining sufficient soft tissue coverage while concurrently obviating additional donor-site morbidity. These spare parts can be utilized as either pedicled or free fillet flaps. This paper describes the unique use of in-continuity chimeric pedicled fillet flaps of the lower extremity to reconstruct and stabilize the pelvic ring, to obliterate dead space, and to provide overlying soft tissue coverage.
Keywords: external hemipelvectomy; fillet flaps; microvascular surgery